Practice Patterns of Physicians Using Adjunct Therapies with Botulinum Toxin Injection for Spasticity: A Canadian Multicenter Cross‐Sectional Survey. Issue 4 (26th August 2020) - Ip, Alvin H.; Phadke, Chetan P.; Boulias, Chris; Ismail, Farooq; Mills, Patricia B.
Abstract : Background: Adjunct therapies are nonpharmacological treatments used with botulinum toxin (BoNT) injection that may improve spasticity outcomes. It has been suggested that physicians consider adjunct therapies as a part of comprehensive spasticity management. It is unclear which adjunct therapies are used by physicians in clinical practice. Objective: To determine physician practice patterns and perceptions of use of adjunct therapies following BoNT injection for limb spasticity. Design: Cross‐sectional national survey of current clinical practice using a 22‐item questionnaire developed by the authors. Setting: Not applicable. Participants: Survey respondents were physicians actively administering BoNT injections for limb spasticity management across Canada (N = 48). Interventions: Not applicable. Main Outcome Measures: Types of adjunct therapies used by physicians; physician opinions on barriers to adjunct therapy use, patient preferences, and future research priorities. Results: Most physicians prescribe home stretching programs, home active exercise programs, and splinting; however, many physicians perceive that these same adjunct therapies are unwanted by patients. A minority of physicians prescribe electrical stimulation (ES), transcutaneous electrical nerve stimulation (TENS), casting, and extracorporeal shockwave therapy; financial limitations and perceived lack of evidence were identified as barriers to their use. Significantly more physicians practicing in academic settings compared with nonacademic, community, and private practice settings used functional ES (59% vs 11%) and TENS (41% vs 0%) as adjunct therapies ( P < .05). Research priorities included determining the effectiveness of immediate postinjection application of adjunct therapies (eg, injected muscle activation with ES or stretching) and nutraceuticals. Conclusions: Canadian physicians frequently use adjunct therapies in combination with BoNT injection to treat spasticity. Financial and time constraints are identified as barriers to implementation of adjunct therapies that are currently supported by research, and patient preferences may also affect compliance. Future research should focus on adjunct therapies that overcome these barriers.